La memoria de la ciudad en TAFOS: antropología visual cuando el otro tiene la cámara (portafolio fotográfico con breve prólogo) - Ramírez Corzo, Daniel (Pontificia Universidad Católica del Perú. Fondo Editorial, 2007)
This paper offers and analyses a selection of pictures —with special emphasis on those representing urban scenes — from the photographic collection of Tafos’ Social Photography Workshop. Its main purpose is to highlight some important issues in contemporary discussion about anthropology in general and visual anthropology in particular: (1) theoretical and methodological issues and aspects associated with the experience developed by TAFOS in the field of visual anthropology, and (2) the role that these pictures may have in the construction of Lima’s collective memory.

En el artículo se presenta y analiza una selección de imágenes de escenas urbanas que forman parte de la colección de fotos del taller de Fotografía Social Tafos. Se busca explicitar algunas inquietudes importantes en el marco de la discusión contemporánea sobre la antropología en general y la antropología visual en particular: (1) las interrogantes y los cuestionamientos teóricos y metodológicos que la experiencia de TAFOS conlleva para la antropología visual y (2) el rol que pueden tener estas imágenes en la construcción de la memoria colectiva de la ciudad de Lima.
The memory of the city in TAFOS: visual anthropology when the other has the camera (photographic portfolio with a short prologue)
Keywords: Antropología visual; Antropología urbana; Fotografía social; Lima; Memoria; Auto-etnografía; https://purl.org/pe-repo/ocde/ford#5.04.03